Population structure and consumption growth: Evidence from National Transfer Accounts - Michael Kuhn; Klaus Prettner (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2015)
We assess the impact of population structure on economic growth. Following recent research, we focus on the generational turnover as a key driver of consumption growth. We characterize the impact of the average birth and death rates on the generational turnover, depending on the age-profile of consumption and on the extent of annuity market imperfection. Using recent data from the National Transfer Accounts on consumption profiles for a number of countries, we assess in a comparative way the sign and magnitude of generational turnover and its impact on consumption growth. We find considerable cross-country variation and trace it back to differences in demographic rates and in the consumption structure.
Keywords: E21; J11; O40; 330; demography; economic growth; generational turnover; National Transfer Accounts